(untitled) (International Journal of Engineering and Computer Science, 2017)
An autonomous car is a driverless car or a robotic car, which uses techniques such as radar, lidar, GPS, odometry and computer vision to sense its environment and to navigate without human input. It uses Vehicle to Vehicle communication (V2V) protocol to communicate and share data with its surrounding vehicles but data hiding cannot be done. In this paper, we implement V2V protocol using ZigBee for privacy in data sharing. ZigBee provides secured communication, transportation of cryptographic key and helps in controlling the devices. It is developed using the basic security framework defined in IEEE 802.15.4. Index Terms-Autonomous,V2V, Zigbee, VANET,AES.